Stranded people; Mythical narratives about the first inhabitants of Mentawai Islands - Tulius, Juniator (UI Scholars Hub, 2012)
In this paper, I examine the stories about the origins of the first inhabitants of the Mentawai Islands. My aim is to understand the perspective of the local community in seeing themselves in the particular place and space where they live in the Mentawai Islands. In my opinion, a set of narrative as a story about the origin of a group of people has a significant value for the development of local communities and their culture. A collection of narratives is an important source of information to understand the ideas of local communities in perceiving their past, especially people who do not have a written tradition. Many of these stories have not been studied thoroughly and on this occasion, I explore it in more depth.